Support for a nicotine reduction policy among participants enrolled in a 20-week trial of very low nicotine content cigarettes. - Denlinger-Apte, Rachel L. (Addict Behav, 2020)
INTRODUCTION: The Food and Drug Administration is considering a policy to drastically reduce the allowable nicotine content of cigarettes. The current study examined whether the policy implementation approach, i.e., either immediately reducing nicotine content to very low levels or gradually reducing nicotine content over an extended period, influences policy support among people who smoke cigarettes. METHODS: Adults who smoked daily were randomly assigned (double-blind) to an immediate nicotine reduction condition (0.4 mg/g nicotine cigarettes), a gradual nicotine reduction condition (15.5 to 0.4 mg/g), or a control condition (15.5 mg/g) for 20 weeks. Participants were asked if they would “support or oppose a law that reduced the amount of nicotine in cigarettes, to make cigarettes less addictive.” Logistic regression analyses assessed if policy support was affected by treatment condition, demographic covariates, interest in quitting, and subjective cigarette effects. RESULTS: At Week 20 (N=957 completers), 60.4% of participants supported the policy, 17.4% opposed, and 22.2% responded “Don’t know.” Policy support did not differ by treatment condition. Support was greater among those interested in quitting (OR=3.37, 95% CI=2.49, 4.55). Support was lower among males (OR=0.49, 95% CI=0.37, 0.67), those with greater dependence scores (OR=0.92, 95% CI=0.86, 0.99) and participants aged 18–24 (OR=0.53, 95% CI=0.28, 0.99). No other covariates were associated with policy support. CONCLUSIONS: The majority of participants supported a nicotine reduction policy. The implementation approach, immediate or gradual reduction, did not affect policy support. Participants interested in quitting smoking were more likely to support a nicotine reduction policy.